1996
DOI: 10.2323/jgam.42.51
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation activities of some new species of anaerobic rumen fungi from Malaysia.

Abstract: The fermentation activities of three new anaerobic rumen fungi, viz, Neocallimastix variabilis, Piromyces spiralis and P. minutus, and a Caecomyces communis isolate grown on straw and filter paper media were studied. N. variabilis, P. spiralis and P. minutus produced carboxymethylcellulase (CMCase), FPase (filter paper activity) and xylanases when grown on straw and filter paper media. C. communis produced only xylanases. The maximum production of all the enzymes was at 72 h of fungal incubation. On both media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In general, polycentric anaerobic fungi produce less lactate compared to monocentric organisms (Gordon and Phillips, 1993). However, some studies reported that Piromyces present in the rumen did not generate any lactate (Ho et al, 1996). Some ARF species were reported to produce an endo-pectin lyase and polygalacturonase (Gordon and Phillips, 1993).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…In general, polycentric anaerobic fungi produce less lactate compared to monocentric organisms (Gordon and Phillips, 1993). However, some studies reported that Piromyces present in the rumen did not generate any lactate (Ho et al, 1996). Some ARF species were reported to produce an endo-pectin lyase and polygalacturonase (Gordon and Phillips, 1993).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…Similarly, Nagpal et al (2009) reported that the FPase enzyme in Caecomyces sp. was higher activity than CMCase, while Ho et al (1996) stated that Filter Paper was pure cellulose which can induce anaerobic fungi to produce enzymes, especially cellulase. The results also showed that all anaerobic fungi isolated from buffalo rumen had the lowest Avicel hydrolysis activity compared to other substrates.…”
Section: Cellulase Enzyme Activity In Anaerobic Fungi Isolated From B...mentioning
confidence: 99%
“…The results in Figure 2 showed that all anaerobic fungi isolated from the rumen of buffalo have increased activity of cellulase (CMCase, Avicelase, and FPase) after passing through the growth lag phase (24 hours). The results of a study conducted by Ho et al (1996) showed that the CMCase and FPase activity of anaerobic fungi types N. variabilis, P. spiralis, P. minutus, and C. communis also increased rapidly after 24 hours. The results also showed that all anaerobic fungi reached optimum conditions at 5 days because the peak of fungal growth occurred at 96-108 hours (4-4.5 days) and enzyme activity was measured every 24 hours.…”
Section: Cellulase Enzyme Activity In Anaerobic Fungi Isolated From B...mentioning
confidence: 99%
See 1 more Smart Citation